2019
DOI: 10.1126/sciimmunol.aay6125
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete genetic reconstitution of B cell pools contributes to prolonged immunosuppression after measles

Abstract: Measles is a disease caused by the highly infectious measles virus (MeV) that results in both viremia and lymphopenia. Lymphocyte counts recover shortly after the disappearance of measles-associated rash, but immunosuppression can persist for months to years after infection, resulting in increased incidence of secondary infections. Animal models and in vitro studies have proposed various immunological factors underlying this prolonged immune impairment, but the precise mechanisms operating in humans are unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 51 publications
4
75
0
2
Order By: Relevance
“…Resulting from the global rise of vaccine hesitancy, one of the 10 threats to global health (52), transmission of measles is rapidly spreading, which poses a significant hazard to children's health. Besides common complications related to measles infection in children, such as diarrhea, middle ear infection and pneumonia (53), it has recently been identified that measles can obliterate existing humoral immune memory against a repertoire of pathogens (54,55). The incomplete reconstitution of the naïve B cell pool and the depletion of previously expanded B memory clones account for this obliteration of immune memory (54).…”
Section: Vaccines Contraindicated For Immunization During Pregnancymentioning
confidence: 99%
“…Resulting from the global rise of vaccine hesitancy, one of the 10 threats to global health (52), transmission of measles is rapidly spreading, which poses a significant hazard to children's health. Besides common complications related to measles infection in children, such as diarrhea, middle ear infection and pneumonia (53), it has recently been identified that measles can obliterate existing humoral immune memory against a repertoire of pathogens (54,55). The incomplete reconstitution of the naïve B cell pool and the depletion of previously expanded B memory clones account for this obliteration of immune memory (54).…”
Section: Vaccines Contraindicated For Immunization During Pregnancymentioning
confidence: 99%
“…Other pathogens may also have an ability to suppress humoral immunity. Recent studies indicated that respiratory syncytial virus (RSV) infection fails to induce in IgA + memory B cells (50) and that measles causes elimination of 11-73% of the antibody repertoire and depletion of previously expanded B memory clones after infection (51,52). However, cellular and molecular mechanisms on their suppression are still unknown and should be investigated, then comparing with the case of Salmonella.…”
Section: Roles Of Humoral Immunity Against Salmonella and New Generatmentioning
confidence: 99%
“…Nonetheless, very recently, Petrova et al [68] identified the long-term consequences of MV infection: Incomplete reconstitution of the naive B cell pool and a compromised immune memory to previously encountered pathogens. Similar results have also been shown by Mina et al [69].…”
Section: Measles and Immunitymentioning
confidence: 99%